THE NEED FOR INFORMATION AND COMMUNICATION TECHNOLOGIES IN AGRICULTURE (World Economics and Finance Bulletin, 2025)
The article examines the use and development of information technologies (hereinafter referred to as IT) in agriculture in Uzbekistan. Agriculture is a long and complex business, requiring large financial investments.
Keywords: Information technology; agribusiness; technology